Leadless pacemaker implantation in patients with a previous transvenous device. (19th May 2022) - Jelisejevas, J; Regoli, F; Hofer, D; Conte, G; Saguner, AM; Caputo, ML; Grazioli, L; Steffel, J; Auricchio, A; Breitenstein, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Leadless pacing has been established as an alternative approach to transvenous devices for selected patients suffering from bradycardias. While in the majority of cases leadless pacemaker implantation represents a de novo procedure, in an increasing number of patients such a device is used after a previously implanted transvenous pacemaker. Purpose: Retrospective analysis of the efficacy and safety outcome in patients who underwent leadless pacemaker implantation in the context of a previously implanted conventional pacemaker. Methods and Results: In this retrospective analysis from two large Swiss implantation centres, 257 consecutive patients undergoing leadless pacemaker implantation were included. Of the total cohort, 233 patients were diagnosed with new-onset bradycardias, while in 24 patients a prior transvenous device was present. Out of these 24 patients, 20 subjects required lead extraction of the previous system due to infection (70%, 14 patients), malfunction or other reasons (Table 1). In 3 patients with device-related infection, lead extraction and leadless pacemaker implantation were performed as a single procedure, while in the remaining 11 cases a time window between the two procedures was present (median of 11.5 days with a range of 2 to 186 days). In the population with a previous device, mean age at implantation was 81 ± 9 years which did not differ compared to the de novo cohort. Mean implantation duration was 57 ± 31 minutes in the cohort with a previous device versus 48 ± 191 minutes in the de novo population without a significant difference (P=NS) and with a successful implantation rate of 100% versus 98.7% in the de novo population (P=NS). Electrical device parameters (sensing, impedance, threshold) at implantation and during follow-up (mean 12.5 ± 9.3 months) were similar between the two groups. Eight major periprocedural complications (3.1%) were encountered (4 pericardial effusions, 3 femoral bleedings and 1 intra-abdominal bleeding) in the entire cohort within a 30 days period, of which the majority occurred in the de novo cohort (75 %, 6 of 8). A total of 4 pericardial effusions occurred, which could be managed without the need for cardiac surgery. The were no reinfections registered after leadless pacemaker implantation during follow-up. Conclusions: Implantation of a leadless pacemaker in patients with a prior conventional system (with or without extraction of the previous device) was effective and safe in our population of patients.